Transparency in Government Political Communication: Challenges and Opportunities - Vera Hermawan (SEAN Institute, 2025)
This study aims to analyze transparency in government political communication, focusing on the challenges faced and the opportunities that can be leveraged. Transparency is a crucial element in building public trust and strengthening government legitimacy in the era of modern democracy. However, the practice of transparency often encounters various obstacles such as the politicization of information, bureaucratic resistance, and low media literacy among the public. On the other hand, the development of information technology, the involvement of civil society, and regulations on information disclosure present strategic opportunities to enhance the transparency of political communication. This study uses a qualitative approach with a literature review method and descriptive analysis of various relevant sources. The findings show that the transparency of government political communication faces serious challenges, including the politicization of information, limited access in various regions, unclear regulations on information disclosure, low capacity of bureaucratic personnel, and the threat of hoaxes due to technological advancements, all of which further erode public trust. Nevertheless, amid these challenges, there are significant opportunities to be seized, such as advances in information and communication technology, increased public participation, demands for democratization, the implementation of e-government and smart city initiatives, the strengthening of openness regulations, and efforts to enhance digital literacy among the population. With the right strategies to manage these challenges and optimize the available opportunities, the government has great potential to achieve more transparent, accountable, and community-oriented public communication.